2019
DOI: 10.1007/s13199-019-00613-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of gut microbiomes in nine species of parrots in captivity

Abstract: Gut microbiomes have profound effects on the health of hosts. About 28% of extant parrot species are threatened with extinction. To inform conservation efforts, we characterized and compared the gut microbiomes in nine species of parrots in captivity. The core gut microbiome of parrots was dominated by three bacterial phyla: the Firmicutes, Proteobacteria, and Actinobacteria. This core gut microbiome is similar to that in other herbivorous birds. There were no statistical differences in the diversity of gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Catellicoccus were first described in 2006 following isolation from decomposing sea mammals (Lawson, Collins, Falsen, & Foster, ) and have subsequently been discovered to be a significant member of the gull faecal microbiome (Koskey, Fisher, Traudt, Newton, & McLellan, ; Lu, Santo Domingo, Lamendella, Edge, & Hill, ). Enterococcus , Staphylococcus , Lactobacillus , Enterobacter , Clostridium and Lactococcus were detected in at least one quarter of the samples and are all common gut microbes in birds (e.g., Grond, Perreau, et al, ; Liu et al, ; van Dongen et al, ; Waite & Taylor, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catellicoccus were first described in 2006 following isolation from decomposing sea mammals (Lawson, Collins, Falsen, & Foster, ) and have subsequently been discovered to be a significant member of the gull faecal microbiome (Koskey, Fisher, Traudt, Newton, & McLellan, ; Lu, Santo Domingo, Lamendella, Edge, & Hill, ). Enterococcus , Staphylococcus , Lactobacillus , Enterobacter , Clostridium and Lactococcus were detected in at least one quarter of the samples and are all common gut microbes in birds (e.g., Grond, Perreau, et al, ; Liu et al, ; van Dongen et al, ; Waite & Taylor, ).…”
Section: Discussionmentioning
confidence: 99%
“…and Lactococcus were detected in at least one quarter of the samples and are all common gut microbes in birds (e.g., Grond, Perreau, et al, 2019;Liu et al, 2019;van Dongen et al, 2013;Waite & Taylor, 2014).…”
Section: Enterococcus Staphylococcus Lactobacillus Enterobacter Cmentioning
confidence: 99%
“…The first phylosymbiosis study on mammalian gut microbiomes [4] demonstrated the effects of animal phylogeny and diet on gut microbial community dissimilarity [12,21,23,39,70,83]. Studies focusing on gut microbiomes of specific animal groups detected phylosymbiosis in American pikas [51] and Peromyscus deer mice [23,52], no phylosymbiosis in western chipmunks [84], and mixed evidence of phylosymbiosis in primates [17,43,44,70], bats [55,85] and birds [62,68,86,87]. A recent large-scale study revealed much stronger effects of host phylogeny and diet on the gut microbiomes of non-flying mammals than those of bats and birds [72].…”
Section: The Prevalence Of Phylosymbiosismentioning
confidence: 99%
“…Several synergistic factors, such as the environment and diet dominate over host genetics in determining gut microbiota composition [29][30][31]. A comparative study of gut microbial diversity among parrot species, indicated the potential role of host ancestry in shaping gut microbiomes [32]. In birds, genetics specialists applied GWASs to demonstrate the relationship between host genotype and gut/reproductive microbiota population [33][34][35][36][37][38].…”
mentioning
confidence: 99%